ANALYSIS OF THE EFFECT OF TAX SOCIALIZATION AND TAX KNOWLEDGE ON INDIVIDUAL TAXPAYER COMPLIANCE AT THE TAX SERVICE OFFICE ,MEDAN PETISAH - Sri Wahyuni; Selvi Aristantya; Etty Harya Ningsi (PT. Radja Intercontinental Publishing, 2026)
The purpose of this study is to analyze the influence of taxpayer socialization, taxpayer knowledge, on individual taxpayer compliance, directly or indirectly by using individual taxpayers and the sample of this study amounted to 50 correspondence people registered as taxpayers at the Medan Petisah Pratama Tax Office. The sampling method used convenience sampling. Data were analyzed using path analysis with SPSS version 19.0. The research results show that tax socialization successfully influences taxpayer compliance. Second, tax knowledge does influence taxpayer compliance. Third, individual taxpayer compliance. Fourth, tax socialization influences taxpayer compliance. Fifth, tax knowledge influences taxpayer compliance.